Perancangan Interior Unit Kesehatan Di Area Skate Park Surabaya (Konsekuensi Alih Fungsi Kontainer Menjadi Wadah Kegiatan) - Yusita Kusumarini, Rarhas Wijayanti (Intra, 2014)
Variousity of Design efforts to reducing the impact of global warming, have been a common features at this time. The heaping up container at the port caused by manufacturing of a new containers is cheaper than shiping back to the place of origin in the empty condition, is the actual fact about container. Container is easy to get and assamble, interesting to be applied, movable, structurally very strong and the important thing is can be reached with a relatively cheap price. Refunctioning container to be an activity places is the one of solution from that problem. The design method adopted from Design Thinking process. The main Consequences of construction using container material, thatâs all about heat insulation. At the other side, public areas such as Skate Park Surabaya be observed from activities classified in extreme sport and require a Healthy unit centre specifically for first Aid with limited space.